Geriatric Nutrition Risk Index is closely associated with sarcopenia and quality of life in gastric cancer patients: a cross-sectional study - Junbo Zuo; Zhenhua Huang; Yan Ge; Xin Ding; Xiuhua Wang; Xiaodong Zhou (Scientific Reports)
Abstract Impaired nutritional status is closely related to the development of sarcopenia and poor quality of life (QoL) in cancer patients. This study aimed to investigate the association of Geriatric Nutritional Risk Index (GNRI) with sarcopenia and QoL in patients with gastric cancer (GC). Sarcopenia was diagnosed based on the Asian Working Group for Sarcopenia 2019 criteria. This cross-sectional study included a total of 311 patients with GC. Among them, 57 (18.3%) patients were diagnosed with sarcopenia. GNRI showed significant correlations with sarcopenia-related indicators including skeletal muscle index, handgrip strength, gait speed, and 5-time chair stand time (p < 0.001). A significant association was observed between GNRI and sarcopenia [odds ratio (OR) = 0.815, 95% confidence interval (CI): 0.760–0.874, p < 0.001] in the multivariate analysis. The optimal cutoff value of GNRI for predicting sarcopenia was 94.98, with a sensitivity of 75.4% and specificity of 73.2%. Patients with low GNRI exhibited significantly lower scores in terms of global health status and most functional scales. Furthermore, the majority of symptoms exhibited greater severity in patients with low GNRI. In conclusion, the present study revealed that GNRI was closely associated with sarcopenia and QoL, and could effectively predict sarcopenia in patients with GC.